Calomys callosus chronically infected by Toxoplasma gondii clonal type II strain and reinfected by Brazilian strains is not able to prevent vertical transmission - Franco, Priscila S.; da Silva, Neide M.; de Freitas Barbosa, Bellisa; de Oliveira Gomes, Angelica; Ietta, Francesca; Shwab, E. K.; Su, Chunlei; Mineo, José R.; Ferro, Eloisa A. V. (Frontiers in Microbiology, 2015)
Considering that Toxoplasma gondii has shown high genetic diversity in Brazil, the aim of this study was to determine whether C. callosus chronically infected by the ME-49 strain might be susceptible to reinfection by these Brazilian strains, including vertical transmission of the parasite. Survival curves were analyzed in non-pregnant females chronically infected with ME-49 and reinfected with the TgChBrUD1 or TgChBrUD2 strain, and vertical transmission was analyzed after reinfection of pregnant females with these same strains. On the 19th day of pregnancy, placentas, uteri, fetuses, liver, spleen and lung were processed for detection of the parasite. Blood samples were collected for humoral and cellular immune response analyses. All non-pregnant females survived after reinfection and no changes were observed in body weight and morbidity scores. In pregnant females, parasites were detected in the placentas of ME-49 chronically infected females and reinfected females, but were only detected in the fetuses of reinfected females. TgChBrUD2 reinfected females showed more impaired pregnancy outcomes, presenting higher numbers of animals with fetal loss and a higher resorption rate, in parallel with higher levels of pro-inflammatory cytokines and IgG2a subclass antibodies. Vertical transmission resulting from chronic infection of immunocompetent C. callosus is considered a rare event, being attributed instead to either reactivation or reinfection. That is, the pregnancy may be responsible for reactivation of the latent infection or the reinfection may promote T. gondii vertical transmission. Our results clearly demonstrate that, during pregnancy, protection against T. gondii can be breached after reinfection with parasites belonging to different genotypes, particularly when non-clonal strains are involved in this process and in this case the reinfection promoted vertical transmission of both type II and Brazilian T. gondii strains.